The Effect of Soil Moisture Content and Animal Manure Application on the Growth of Mendong (Fimbristylis globulosa (Retz.) Kunt) - Yaya Sunarya; Enok Sumarsih (UNIVERSITY OF LAMPUNG, 2017)
The objective of the research was to study the interaction between soil moisture content and animal manure application on the growth of Mendong (Fimbristylis globulosa (Retz.) Kunt). The experiment was conducted in May until September 2016 in Kampung Lembur Sawah, Kamulyan Village, Manonjaya Subdistrict, Tasikmalaya Regency. A pot experiment was performed using a factorial design consisting of two factors and three replicates. The factors were soil moisture content (K) consisting of four levels i.e. k1 (100% field capacity (FC)), k2 (150% FC), k3 (200% FC), and k4 (250% FC); and animal manure application (P) consisting of p1 (cattle manure), p2 (broiler chicken manure), and p3 (sheep manure). The indicators of plant growth, i.e. plant height, number of tiller, fresh weight and dry weight of plant biomass, shoot/root ratio, percentage of the >75cm-long stems, water consumption, and water use efficiency (WUE) were measured. The results showed that there was an interaction effect between the soil moisture content and animal manure application on the number of tiller at 45 days after planting (DAP), the percentage of the >75 cm-long stems, and the water consumption. The sheep manure application at any levels of soil moisture content resulted in better effect on the growth of Mendong, water use efficiency, and quality of stem (the percentage of the >75cm-long stems). The soil moisture content above the field capacity resulted in better effect on the growth of Mendong, indicating that Mendong is more suitable to grow on the land with the soil moisture content above the field capacity or saturated soil during the whole growing period. Keywords: Manure, Mendong, soil moisture content